Preparation and Characterization of Gadolinium Substituted Barium Hexaferrite by High Energy Ball Milling - Kumar, Deepak (My University, 2010)
Among the class of permanent magnets, barium ferrite permanent magnet is the cheapest with moderate magnetic properties. Extensive research has been carried out to study the effect of the various process parameters on the magnetic properties, microstructure and phase present. Various method which includes soild state method, chemical method, HEBM method has been adopted for making hexaferrites. In aforementioned processing method different precursors has been used. However, formation of hexaferrite from monoferrite has not been reported. In the present work
M.Tech. (Materials and Metallurgical Engineering)
Keywords: hexaferrites